Measuring the quality of maternal and care processes at the time of delivery in sub-Saharan Africa: development and validation of a short index - Vandana Tripathi; Cynthia Stanton; Donna Strobino; Linda Bartlett (BMC, 2019)
Abstract Background There is a growing recognition that quality of care must improve in facility-based deliveries to achieve further global reductions in maternal and newborn mortality and morbidity. Better measurement of care quality is needed, but the unpredictable length of labor and delivery hinders the feasibility of observation, the gold standard in quality assessment. This study evaluated whether a measure restricted to actions at or immediately following delivery could provide a valid assessment of the quality of the process of intrapartum and immediate postpartum care (QoPIIPC), including essential newborn care. Methods The study used a comprehensive QoPIIPC index developed through a modified Delphi process and validated by delivery observation data as a starting point. A subset of items from this index assessed at or immediately following delivery was identified to create a "delivery-only" index. This delivery-only index was evaluated across content and criterion validation domains using delivery observation data from Kenya, Madagascar, and Tanzania, including Zanzibar. Results The delivery-only index included 13 items and performed well on most validation criteria, including correct classification of poorly and well-performed deliveries. Relative to the comprehensive QoPIIPC index, the delivery-only index had reduced content validity, representing fewer dimensions of QoPIIPC. The delivery-only index was also less strongly associated with overall quality performance in observed deliveries than the comprehensive QoPIIPC index. Conclusions Where supervision resources are limited, a measure of the quality of labor and delivery care targeting the time of delivery may mitigate challenges in observation-based assessment. The delivery-only index may enable increased use of observation-based quality assessment within maternal and newborn care programs in low-resource settings.